Corrigendum: Xiaoyaosan alleviates hippocampal glutamate-induced toxicity in the CUMS rats via NR2B and PI3K/Akt signaling pathway - Zhou, Xueming; Liu, Chenyue; Liu, Yueyun; Ma, Qingyu; Zhao, Xin; Jiang, Youming; Li, Xiaojuan; Chen, Jia-Xu (Frontiers in pharmacology, 2022)
[This corrects the article DOI: 10.3389/fphar.2021.586788.].